Mitigação de efeitos deletérios do alumínio tóxico por bactérias promotoras de crescimento vegetal na cultura do trigo [Triticum aestivum (L.) Thell] - Cardoso , Kerolém Prícila Sousa (2021)
The solubility of phytotoxic aluminum in soils causes limitations in crop performance, affecting the root system and later the shoot, with a reduction in plant growth and development factors. Thus, the use of plant growth promoting bacteria (BPCV) has gained prominence due to its use as a more sustainable management technology, favoring the search for reducing the harmful effects caused by aluminum. Thus, this study aimed to evaluate biochemical responses and photosynthetic, biometric and yield effects in wheat cultivars inoculated with Azospirillum brasilense and Pseudomonas fluorescens and subjected to the presence of phytotoxic aluminum. The experiment was carried out in a randomized block design, in a factorial arrangement 3 wheat cultivars x 4 growing conditions, with four replications. Electrolyte leakage in leaf and root tissues, as well as the levels of nitrate, free ammonium, N-aminosoluble, total soluble proteins, proline and glycine-betaine are reported. They were also measured as gas exchange and Spad index, in addition to biometric variables and production components. There was a significant increase in electrolyte leakage when the cultivars were subjected to aluminum, this effect being attenuated by the inoculation of BPCV. For the levels of nitrate and ammonium there was a significant difference between the cultivars; the content of total soluble proteins was reduced in the presence of aluminum and those of N-aminosoluble proteins did not change. Compatible osmolyte rules increased above 20% with inoculation. There was an increase in photosynthetic, biometric and production performance when the cultivars were inoculated with bacteria in soil with the presence of aluminum. Inoculation with Pseudomonas fluorescens provided the best attenuation and a BRS Sanhaço cultivar better positioning in soil with the presence of phytotoxic aluminum, resulting in a reduction of photosynthetic and biochemical damage.